Management of Prosthetic Valve Thrombosis and its Clinical Profile in the Cardiac Center of Pakistan - Faizan Ahmed, Mohsin Shabir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The one of the highly known life threatening complication of the post valve replacement surgeries is prosthetic valve thrombosis. The poor anticoagulation status is the reason behind this thrombotic complication. Objective: The study aimed to study the management of prosthetic valve thrombosis in the teaching hospital of our institute. The clinical profile of the patients was also evaluated. Study design: It is an observational study aided with the statistical approaches, conducted in cardiology department of Rehman Medical Institute Peshawar. Material and Methods: The study was conducted at the cardiology department of our hospital. The 40 patients who attended the cardiology department from May 2021 to May 2022 were selected for the study. According to the inclusion criteria the patients diagnosed with the PV thrombosis were selected for further study. The demographic profile and clinical parameters of each patient was recorded. The in hospital outcomes were also analyzed. Results: The diagnosis was further confirmed by using fluoroscopy. The age group of the patients suffering from PV thrombosis was from 10 to 68 years with an average age of 35 years. Out of 40 patients added in the study, majority were female participants (60%). Among all the patients chosen for study, there were 88% that were admitted to the hospital after 1 week of symptoms. The shortness of breath and related symptoms were reported in 95% of the patients. The most common sort of treatment used for all the patients was thrombolysis, it was carried out for 93% of the patients. Conclusion: The PV thrombosis is a clinical emergency and it is linked with high mortality rate. Low socio-economic status results in poor compliance of the anti-coagulation treatment. The treatment guidelines for PV thrombosis are updated on daily basis, so for better drug compliance, proper follow-up of the disease is needed. For the management of prosthetic valve thrombosis the thrombolysis is considered as a useful option.